Five new species of Terebellides (Annelida, Polychaeta, Trichobranchidae) from Papua New Guinea (Bismarck and Solomon seas) - Lavesque, Nicolas; Nogueira, João M. M.; Daffe, Guillemine; Hutchings, Pat (Frontiers in Ecology and Evolution, 2024)
Five new species of Terebellides are described from coastal and deep waters of Papua New Guinea, using both morphology and molecular tools (for four species). Terebellides elenae n. sp. is characterized by the absence of both a glandular lateral region on TC3 and papillae on margins of the branchial lamellae and by the presence of partially fused branchial lobes with conspicuous fifth lobe and dorsal rounded projections until TC6. Terebellides fauchaldi n. sp. has a very large glandular lateral region on the third thoracic chaetiger (TC3), a fifth branchial lobe and partially fused branchial lobes, and conspicuous dorsal rounded projections on TC2–6. Terebellides madeep n. sp. is characterized by a thin glandular region on TC3 and by four free branchial lobes. Terebellides oculata n. sp. is one of the only two species in the world to have eyespots. Finally, T. papillosa n. sp. has geniculate chaetae on TC6 and TC7 and bears a large number of papillae. A majority-rule consensus tree using the 16S gene and an identification key for all Terebellides species described from the Central Indo-Pacific region are provided.